Truthful Relay Assignment for Cooperative Communication in Wireless Networks with Selfish Source-Destination Pairs. (12th November 2012) - Liu, Gang; Huang, Liusheng; Sun, Yu-e; Xu, Hongli; Huang, He; Xu, Xueyong
Abstract : Cooperative communication is shown to be a promising technology to significantly increase the capacity of wireless networks. Due to the competition among multiple source-destination pairs for the same relay node set in the relay assignment problem, each pair may cheat others to achieve a more individual revenue. However, the cheating behavior may decrease the overall performance of the network greatly. Thus, there is a challenge for designing a truthful protocol that maximizes a pair's payoff only when this pair reveals its true individual information. In this paper, we propose a relay assignment protocol (RA-VCG) for cooperative communication to maximize the total social value (i.e., the total true value of all pairs) while guaranteeing truthfulness in an auction-theoretic sense by charging each pair an extra payment. Specially, RA-VCG implements a variation of the well-known VCG mechanism for the truthful relay assignment problem in the network with selfish source-destination pairs. Then, we prove the validity of this protocol and also show several surprising properties (such as no positive transfer and individual rationality) associated with this protocol. The simulation results show that the total social value achieved when each node takes untruthfully is about 23.3% less than that achieved when nodes behave truthfully.